Current morphology - Carstairs-McCarthy, Andrew, 1945- (Linguistic theory guides., 1992)
This book aims to provide a thorough and wide-ranging introduction to approaches to morphology in linguistic theory over the last twenty years. This comprehensive survey concentrates not only on the generative linguistic mainstream, but on approaches that are less fashionable or relatively unknown to English-speaking linguists, and highlights recent European, particularly German-speaking research.